Effect of nitrogen levels and planting geometry on growth, herbage and oil yields of patchouli (Pogostemon cablin Benth.) under humid sub-tropical climate of North Eastern Himalayas - Saha, Poulami; Chaudhuri, Arindam; Yadav, Gulab Singh; Babu, Subhash (Annals of Agricultural Research, 2016)
A field experiment was carried out during February - July 2012, at Nagicherra, (Tripura West), to study the effect of nitrogen levels and plant geometry on growth, herbage and oil yield of patchouli under humid sub-tropical North Eastern Himalayan Region of India. Results revealed that application of 140 kg N/ha under square planting (50 × 50 cm spacing) produced highest fresh herbage, dry herbage, oil yield and essential oil content as compared to all other nitrogen levels and planting geometry.